POWOŁANIE JAKO PODSTAWA NAWIĄZANIA STOSUNKU PRACY DYREKTORA PRZEDSIĘBIORSTWA PAŃSTWOWEGO - Duraj, Tomasz (Zeszyty Prawnicze, 2016)
Appointment as the Basis for Establishing Employment Relationship of a Director of a State Enterprise Summary The subject of this study is a detailed characteristics of the act of appointment as the basis for employment relationship of a director of a state enterprise. The director is the most important managing and executive body of a state enterprise, and the legal status of a director is regulated by the State Enterprises Act of 25 September 1981 .In relation to a director of a state enterprise there is a special situation, within which there is a legal obligation to utilize the employment relationship by appointment as the basis for employment. It is the only admissible legal relation, on the basis of which a director can work for a state enterprise. The employee status of a director of a state enterprise is primarily regulated by the labor code regulations regarding appointment (articles 68-72 of the labor code), while, according to article 69 of the labor code, to this employment relation – with some exceptions –the regulations regarding employment contracts for an unspecified time are also applicable. In this article the author analyses the issue of establishing and terminating the employment relation with a director of a state enterprise. Particular attention ought to be paid to the specific situation of a director of a state enterprise with regard to the stabilization of his or her employment. It is significantly more advantageous as compared to the situation of other employees employed by appointment. According to the regulations in force, there are no reservations to the principle of removing persons from the posts filled within the institution of appointment in any time and without the necessity to indicate any causes. However, this principle is limited with relation to a director of a state enterprise, due to the specific procedures of dismissal of this category of employees statutory by the act of state enterprises as well as additional rights to which a dismissed director is entitled, especially the right for a dismissal allowance.